Physical, mechanical, and morphological characteristics of soybean fibers - Arya Mahendra Sakti; Djarot B. Darmadi; Femiana Gapsari; Teguh D. Widodo (Case Studies in Chemical and Environmental Engineering, 2024)
Soybean stem waste can be transformed into soybean fibers for polymer composites using alkali treatment as a sustainable solution to address the significant problem of soybean waste availability. SF density and thermal resistance increased with the raise in NaOH concentration. The highest crystallinity index and cellulose content were found at 3% NaOH concentration. Compared to untreated SF, the tensile strength of the SF treated with 3% NaOH improved significantly to 180.99%. The study indicates that SF treated with NaOH has significant potential as a polymer composite reinforcement, potentially replacing synthetic and natural fibers.